2010
DOI: 10.1507/endocrj.k09e-313
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus in a Japanese Girl with HDR Syndrome and GATA3 Mutation

Abstract: Abstract. We report on a japanese girl with hdr (hypoparathyroidism, sensorineural deafness, and renal dysplasia) syndrome who developed diabetes mellitus (dM) at three years of age (blood glucose 713 mg/dL, hba 1c 8.0%) in the absence of anti-glutamic acid decarboxylase autoantibodies. Mutation analysis revealed a de novo heterozygous two base pair deletion at exon 6 of the GATA3 gene (c.1200_1201delca; p.h400fsX506). GATA3 expression was identified by PCR amplification for human pancreas cDNA, and mouse Gata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…A previously reported Japanese patient with a similar frameshift mutation in exon 6 of the GATA3 gene (c.1200_1201delCA; p.H400fsX506) characteristically showed insulin dependent diabetes with a more severe renal anomaly compared to our patient [ 20 ]. In addition to these phenotypic differences, the variant in our patient was different from most other reported GATA3 frameshift mutations.…”
Section: Discussionsupporting
confidence: 51%
“…A previously reported Japanese patient with a similar frameshift mutation in exon 6 of the GATA3 gene (c.1200_1201delCA; p.H400fsX506) characteristically showed insulin dependent diabetes with a more severe renal anomaly compared to our patient [ 20 ]. In addition to these phenotypic differences, the variant in our patient was different from most other reported GATA3 frameshift mutations.…”
Section: Discussionsupporting
confidence: 51%
“…In an extensive review of the literature, we found 173 reported patients. In this report, we review these patients and an additional seven patients observed by the authors (A. Y. Barakat, personal communication, 2017) for a total of 180 patients (Adachi, Tachibana, Asakura, & Tsuchiya, ; Aksoylar et al, ; Ali et al, ; Al‐Shibli, Al Attrach, & Willems, ; Bahceci, Salgur, Tutuncuoglu, Yilmaz, & Oruk, ; Barakat, D'Albora, Martin, & Jose, ; Beetz et al, ; Belge et al, ; Bernandini et al, ; Bilous et al, ; Boysan et al, ; Chen et al, ; Chenouard et al, ; Cheon, Kim, & Yoo, ; Chiu, Chen, Chao, Yann, & Tsai, ; Chu et al, ; Civan et al, ; Doneray, Usui, Kaya, & Dönmez, ; Ferdoush, Mutanabbi, Talukder, Al Helal, & Kawser, ; Fernández et al, ; Ferraris et al, ; Fujimoto et al, ; Fukami et al, ; Gaynor et al, ; Gomes et al, ; Goodwin, Hawley, & Miller, ; Hameed et al, ; Hasegawa et al, ; Hernández et al, ; Higuchi et al, ; Kamezaki et al, ; Kato, Wada, Numata, & Kakizaki, ; Kim et al, ; Kostoglou‐Athanassiou, Stephanopoulos, Karfi, & Athanassiou, ; Lichtner et al, ; Maleki, Bashardoust, Alamdri, & Tavosi, ; Maloo ; Meena, Maloo, Samar, Ruhela, & Saini, ; Melis et al, ; Mino et al, ; Moldovan, Carvalho, Jorge, & Medeira, ; Muroya et al, ; Muroya et al, ; Mutlu, Kırmızıbekmez, Nakamura, Fukami, & Hatun, ; Nakamura et al, ; Nanba et al, ; Nesbit et al, ; Ni & Htet, ; Ohta et al, ; Pollak‐Hainz, Bartsch, Zechner, & Keilmann, ; Ranjbar‐Omrani, Zamiri, Sabayan, & Mohammadzadeh, ; Rodriguez Benitez et al, ; Sau, Chat...…”
Section: History Of the Syndromementioning
confidence: 99%
“…Similar to most phenotypic syndromes, several additional features have been described in association with the syndrome. Among others, hypergonadotropic hypogonadism, polycystic ovaries, congenital heart disease, facial abnormalities, cerebral infarctions, retinitis pigmentosa, basal ganglia calcifications, severe cognitive disability, and autism (Adachi et al, ; Al‐Shibli et al, ; Civan et al, ; Hasegawa et al, ; Hernández et al, ; Kato et al, ; Lichtner et al, ; Meena et al, ; Muroya et al, ; Nesbit et al, ; Taslipinar et al, ; van der Wees et al, ; Verri et al, ; Zahirieh et al, ). Neuropsychological and behavioral abnormalities have been observed in patients with basal ganglia calcification, often present in primary “H.” These calcifications may lead to changes in the fronto‐limbic basal ganglia causing neurological and psychiatric disorders including impaired cognitive function, psychosocial dysfunction, and depression, especially in adult patients (Al‐Shibli et al, ; Civan et al, ; Nanba et al, ).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…Patients with rare defects in the gene encoding GATA3 have hypoparathyroidism, sensorineural deafness, and renal disease (HDR) (MIM 146255) resulting from decreased GATA3 function [10]. In one case report, a pediatric HDR patient also developed type I diabetes [11]. The studied GATA3 mutations result in loss of function [12, 13], with one missense mutant in a DNA-binding domain causing a dominant negative [14].…”
Section: Introductionmentioning
confidence: 99%